2019
DOI: 10.1186/s40792-019-0662-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomy after transcatheter aortic valve implantation in an elderly patient with obstructive descending colon cancer and severe aortic stenosis: a case report

Abstract: Background The demand for laparoscopic colectomy is increasing due to greater number of elderly colon cancer patients, and it is important to evaluate existing comorbidities to ensure perioperative safety. Aortic stenosis (AS) is one of the most common heart diseases in the elderly, and elderly cancer patients with severe AS may be considered ineligible for optimal cancer treatment if they cannot endure surgical aortic valve replacement (SAVR). Recently, transcatheter aortic valve implantation (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…However, TAVI is potentially useful for such patients. While there are several reports of cancer surgery after TAVI ( 8-12 ), to our knowledge, this is the first report of TAVI for a patient undergoing oral cancer surgery. Moreover, there is little data on the feasibility of TAVI for severe AS patients scheduled for cancer surgery and the impact on subsequent surgery.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, TAVI is potentially useful for such patients. While there are several reports of cancer surgery after TAVI ( 8-12 ), to our knowledge, this is the first report of TAVI for a patient undergoing oral cancer surgery. Moreover, there is little data on the feasibility of TAVI for severe AS patients scheduled for cancer surgery and the impact on subsequent surgery.…”
Section: Discussionmentioning
confidence: 78%
“…As far as we are aware, there have been no reports of TAVI being performed before surgery for head and neck cancers. There were a few reports found of TAVI procedures performed before surgery for cancers in other parts of the body ( 8-12 ). The interval between AS treatment and cancer treatment should be short to prevent malignant tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a report of shorter ACT (180–200 s) being applied for TAVI in a patient with pulmonary artery pseudoaneurysm [ 6 ] and a report of TAVI being performed with a shorter ACT (180–200 s) through carotid artery access under local anesthesia in 19 patients [ 7 ]. There have been two reports of TAVI being performed in patients with malignant tumors [ 8 , 9 ]. In those reports, while the authors reported single antiplatelet therapy during malignant tumor surgery after TAVI, there was no description of ACT.…”
Section: Discussionmentioning
confidence: 99%